The Effect of Good Corporate Governance Mechanism and Firm Size on Firm Value in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period - Widyo Nugroho; Septia Hairunissa Budiman (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
This study aims to determine and analyze the effect of institutional ownership, managerial ownership, independent commissioners, and firm size on the firm value of property and real estate sector companies listed on the Indonesia Stock Exchange from 2015 to 2019. The research method used was a secondary method with a quantitative approach. The sample size was 10 companies purposively selected from 77 companies. and the sample used was 10 companies. The data testing used the Multiple Linear Regression test aided with the IBM SPSS Version 23 program. The findings indicate that independent commissioners affect firm value, while institutional ownership, managerial ownership and firm size have no effect on firm value.